Barriers and facilitators of physical activity among Latina immigrant and Mexican mothers living in the US and Mexico: A qualitative study. - Nancy Jacquelyn Pérez-Flores; María Pineros-Leano; Katherine Damian; Ashley M Toney; Liliana Aguayo (PLoS ONE)
Latina immigrant women are among the least physically active when compared with women in other racial/ethnic groups in the US. Similarly, Mexican mothers in Mexico have low rates of physical activity. Motherhood and immigration experiences are recognized barriers to engage in physical activity among Latina immigrant mothers. Less is known about the factors that promote and limit physical activity engagement among Mexican mothers in Mexico, and how their experiences compare with their immigrant counterparts. This transnational qualitative study aimed to investigate the barriers and facilitators of physical activity of 25 Latina mothers in Mexico and the US. Low-income Mexican mothers of kindergarten aged children and Latino mothers of similar aged children were recruited in San Luis Potosí, Mexico and central Illinois, US. Semi-structured interviews were administered by two bilingual and bicultural researchers in participants language of preference. Interviews were transcribed verbatim and analyzed using a thematic network approach and multi-stage coding analysis guided by the Socio-Ecological Model framework. We found that at the macro-level: 1) familial obligations, and 2) cold weather after migrating; at the mezzo-level: 1) changes in walking patterns, and 2) social cohesion (e.g., lack of an invitation to engage in activities); and at the micro-level: 1) individual perceptions, particularly unattainable perceptions of physical activity and 2) shift exhaustion were perceived as barriers and occasionally facilitators of physical activity by mothers in both countries. Context-specific interventions are needed to increase women's physical activity levels in the US and Mexico.